Central Industrial District as an Attempt to Implement the Principles of Sustainable Development in the Inter-War Period Poland - Grata, Paweł (European Journal of Sustainable Development, 2019)
The interwar Poland was a poorly developed and unevenly developed country. The difference between regions was well to see between well-industrialized and so-called western “Poland A” and backward, agricultural and poor “Poland B” in the east. In the second half of the thirties of the twentieth century, Deputy Prime Minister Eugeniusz Kwiatkowski proposed taking action to eliminate the development differences between individual parts of the country. The government decided to build the Central Industrial District (COP), which was located in backward areas located in the central part of the country. The aim of the project was to implement a number of industrial and infrastructure investments and to make the first step on the way to blur the differences between “Poland A” and “Poland B”. Further, the creation of another industrial district east of the COP was assumed. In 1938, E. Kwiatkowski announced the so-called Fifteen-year plan, which was to bring the level of economic development to the level of the entire country until 1954. The large-scale implementation of investment under the COP was interrupted by the outbreak of World War II, but it turned out that the investments undertaken in the second half of the 1930s had a lasting effect. Established in this period, enterprises still play an important role in the economy of present-day south-eastern Poland (Podkarpacie region) and constitute an important element on the way to sustainable development of the country. Keywords: Second Polish Republic, Central Industrial District, state modernization, leveling of development, Eugeniusz Kwiatkowski